A teoria da atividade como referencial teórico metodológico para uma prática pedagógica indispensável à formação humana - Giaretton, Francielly Lamboia (2015)
This research presents a theoretical and conceptual study toward understanding the Activity Theory as a theoretical framework for understanding and possible articulation of a pedagogical practice that allows the conscious development of the subjects. Has as object of study the pedagogical practice, with the overall objective to point the Activity Theory contributions, as proposed by Alexei Nicolaievich Leontiev, to reclassify the practice. This study provides some subsidies that contribute to articulate the Activity Theory to a pedagogy that enables elements to the gradual and qualitative transformation of pedagogical practice and contribute effectively to the conscious development of both teaching activity as the study activity. It starts with the assumption that the category 'activity' has elements able to guide a differentiated focus on the pedagogical practice, optimizing both the teaching activity as the study activity from the understanding that to be an activity is required a reason, which should be achieved through numerous coordinated actions, each with specific objectives. This work is organized in three sessions. The first analyzes the philosophical assumptions underlying the Activity Theory, trying to understand the work as a central category in human development and as a fundamental activity in the appropriation of the world. The second session, brings up the general structure of "activity", which is made up of actions, operations, need, motive and object. To understand these elements becomes essential because it allows also to understand the structure and the development of consciousness. Understood these elements, it is necessary to define the pedagogical practice. This research is based on the assumptions of the Historical-Critical Pedagogy, which meant that school is the proper space for the socialization of historically accumulated knowledge presented at the third session. The aim is to further reflect on how teaching practice can contribute to this conscious development, since it understands the relationship between the appropriation of scientific knowledge and the development of the human psyche as a result of a long historical process pervaded by the relations established in the work, and that this ownership can only ensure maximum development of human capabilities, allowing the overcoming of production relations that limit human development